Controversial types of travel and the position of Polish tourism service providers: Experience tourism - Godlewski, Grzegorz (Turyzm/Tourism, 2019)
The aim of this study is to investigate the potential of the Polish market for the development of the supply-side of controversial forms of tourism, based on the opinions and products offered by tour operators and retail travel agents. Analytical data were collected using desk research and CATI (N=107) methods. The most common controversial types of tourism include drug and sex tourism, followed by disaster tourism, medical tourism, slum tourism, fan tourism and poverty tourism. The expectations of customers regarding tourism offers usually focus on party tourism and extreme travel, and the providers highlight that this market segment will continue to develop.